Progreso de la Impresión 3D de Dispositivos Médicos. - Valenzuela-Villela, K. S.; García-Casillas, P. E.; Chapa-González, C. (Revista Mexicana de Ingeniería Biomédica, 2020)
Transplant of organs and tissues to solve injuries and defects is a problem that must be resolve urgently, because there are difficulties in the process, such as the shortage of donors and the risk caused by immunological rejection. The implantation of artificial organs and tissues suggests a better quality of life in patients, however, it requires a manufacturing technique that allows the development of complex structures. The 3D printing technique offers to solve the current limitations in the development of organs and tissues, allows the incorporation of cells in biomaterials for the regeneration of biological structures. This review summarizes the most relevant studies and progress in the development of implants, prosthesis and tissue engineering using 3D printing, introducing to the different biomaterials used in additive manufacturing, as well as printing techniques used in biomedical applications.